Penguatan Nilai Karakter Dalam Pembelajaran Pendidikan Agama Islam Siswa SMP Negeri 8 Palangka Raya - Ulandari, Sri; Hartati, Zainap; Anshari, Muhammad Redha (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study aims to identify and analyze the strengthening of character values in Islamic Religious Education learning for students at SMP Negeri 8 Palangka Raya. The character values in question include aspects such as religious, honesty, discipline, responsibility, curiosity and environmental care by using character strengthening strategies through advice methods, exemplary methods and habituation methods which are considered essential in forming students with noble character and good personality. The research method used is qualitative. Data were collected through structured interviews, observations, and documentation. The results of the study indicate that the application of character values in Islamic Religious Education Learning at SMP Negeri 8 Palangka Raya is carried out through various forms of reinforcement, including the integration of values in Islamic Religious Education learning. In conclusion, strengthening character values in Islamic Religious Education learning has a positive impact on the development of students' character, although there are several challenges that need to be overcome, such as limited time and support from the family environment. This study provides recommendations for the development of more comprehensive and sustainable learning programs to increase the effectiveness of strengthening character values in religious education.